Clinical characteristics, management, and prognosis of pembrolizumab-induced immune-related oral mucositis - Yu, Liuxian; Li, Jun; Tang, Yaxi (Frontiers in Immunology, 2026)
BackgroundPembrolizumab-induced immune-related oral mucositis (irOM) is a rare and often underrecognized toxicity. This study aimed to systematically characterize its clinical profile, histopathologic patterns, management strategies, and outcomes to support timely diagnosis and evidence-based care.MethodsA comprehensive search of PubMed, EMBASE, Web of Science, WanFang Data, and CNKI was performed using a combination of MeSH terms (e.g., “Pembrolizumab,” “Oral Mucositis,” “Stomatitis,” “Mucous Membrane Pemphigoid,” and “Immune-Related Adverse Events”) and free-text terms (e.g., “anti-PD-1” and “checkpoint inhibitor toxicity”), with Boolean operators (AND/OR) applied to maximize retrieval; reports published up to July 31, 2025, were included. The quality of case reports was evaluated using the JBI Critical Appraisal Checklist.ResultsAmong 18 patients, the median age was 72 years (range 15, 88) and 72.2% were male. The median onset of irOM was 24 weeks (range 3, 66), consistent with a delayed presentation. Clinically, painful oral ulcers or erosions were most frequently observed (50.0%), followed by dysphagia or odynophagia (27.8%). Histopathologic evaluation most often revealed a pemphigoid-like pattern (27.8%) or mixed inflammatory infiltrates (22.2%), with additional findings including ulceration with granulation tissue, lichenoid mucositis, plasma cell infiltrates, and epithelial hyperplasia. Systemic corticosteroids were the mainstay of therapy (88.9%), while pembrolizumab was discontinued in one-third of cases (33.3%). Refractory disease occasionally required immunomodulatory agents such as methotrexate (16.7%) or infliximab (11.1%). Clinical outcomes were generally favorable, with 88.9% of patients achieving symptomatic improvement or remission and a median recovery time of 6 weeks (range 2, 52). On rechallenge, 3 of 4 patients had no recurrence.ConclusionPembrolizumab-induced irOM usually develops after months of treatment, presenting as ulcerative mucositis, sometimes extending to the airway or esophagus. Biopsy may show pemphigoid-like changes. Corticosteroids are effective, and immunosuppressants can be used for refractory cases. Recovery is typically within weeks and rechallenge is feasible for select patients.